Study of the efficacy of Galactin Vet Bolus on milk yield in dairy cows - Baig M.I. and Bhagwat V.G. (Veterinary World, 2009)
Efficacy study of GALACTIN VET bolus (5 boli once daily for 10 days) was conducted in moderate milk producing Holstein and Jersey crossbred cows. Improved Milk yield, CLR, Fat % and SNF % supported GALACTIN VET bolus to be safe galactogogue in dairy cows. [Vet. World 2009; 2(4.000): 140-142]